2007
DOI: 10.2174/138161207780618975
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide in Neurodevelopmental Disorders:Therapeutic Potential

Abstract: Abstract:Vasoactive intestinal peptide (VIP) mediates important events during the development of the nervous system. VIP can stimulate neuronogenesis as well as differentiation and neurite outgrowth; it can promote the survival of neurons and assist in neuronal repair; it is also anti-inflammatory and can modulate immune responses. In addition, VIP is necessary for the normal growth and development of the early postimplantation mouse embryo during the period when the major embryonic events are neural tube form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 128 publications
(183 reference statements)
3
33
0
Order By: Relevance
“…While not extensively studied in central neurons, VIP is a neurotrophic factor that can regulate neural growth, migration, and process formation. [29][30] In our current study, we deduced that abnormal visual stimulation may reduce the production of endogenous VIP, and then the cortical energy metabolism and the supply of metabolic substrates are influenced. Confirmed in the present study is that asymmetrical visual stimulation during the development of the visual cortex may cause amblyopia through reduction of VIP synthesis in the cortex.…”
Section: Discussionmentioning
confidence: 71%
“…While not extensively studied in central neurons, VIP is a neurotrophic factor that can regulate neural growth, migration, and process formation. [29][30] In our current study, we deduced that abnormal visual stimulation may reduce the production of endogenous VIP, and then the cortical energy metabolism and the supply of metabolic substrates are influenced. Confirmed in the present study is that asymmetrical visual stimulation during the development of the visual cortex may cause amblyopia through reduction of VIP synthesis in the cortex.…”
Section: Discussionmentioning
confidence: 71%
“…During development, VIP promotes neurogenesis, differentiation of other cell types in the nervous system, neurite outgrowth, and mediates neuronal survival (Hill 2007). We have previously shown that ADNP expression increases in the SGZ of the DG (Cosgrave et al 2008), the site of adult neurogenesis, suggesting that it may play an important role in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, a deficit in social behavior has been observed following a blockage of VIP during neural tube closure. This is analogous to the period in human development during which the improper neural development resulting in ASD is thought to occur [59]. Therefore, the strong associations between VIP and ASD suggest that this pluripotent peptide could have pharmacotherapeutic potential.…”
Section: Introductionmentioning
confidence: 94%
“…Studies of affected families and twins have indicated that ASD is highly genetic, as the relative risk of having a second child with ASD, particularly if both children are male, is 20–50 times higher than the population base rate [58]. In terms of environmental causes, incidents of ASD have been linked to thalidomide or valproic acid exposure, prenatal alcohol use, infections, and vaccinations [59]. However, it is likely that susceptibly to ASD is due to many interacting genes with the resulting phenotype modified by complex environmental factors [60].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation